Circulating Placental Alkaline Phosphatase Expressing Exosomes in Maternal Blood Showed Temporal Regulation of Placental Genes - Parveen, Arshiya; Mishra, Suman; Srivastava, Medha; Chaudhary, Dharmendra K.; Kapoor, Deepa; Gupta, Amrit; Tiwari, Swasti (Frontiers in Medicine, 2021)
Background: Analysis of placental genes could unravel maternal-fetal complications. However, inaccessibility to placental tissue during early pregnancy has limited this effort. We tested if exosomes (Exo) released by human placenta in the maternal circulation harbor crucial placental genes. Methods: Placental alkaline phosphate positive exosomes (ExoPLAP) were enriched from maternal blood collected at the following gestational weeks; 6-8th (T1), 12-14th (T2), 20-24th (T3), and 28-32th (T4), Nanotracking analysis, electron microscopy, dynamic light Scattering, immunoblotting were used for characterization. We used microarray for transcriptome and qPCR for gene analysis in ExoPLAP. Results: Physical characterization and presence of CD63 and CD9 proteins confirmed successful ExoPLAP enrichment. Four of the selected 36 placental genes did not amplify in ExoPLAP, while 32 showed regulation (n=3-8/time point). Most genes in ExoPLAP showed significantly lower expression at T2-T4, relative to T1 (p<0.05), including NOS3, TNFSF10, OR5H6, APOL3, NEDD4L. In contrast, genes, including ATF6, NEDD1, IGF2, had significantly higher expression at T2-T4 relative to T1. Unbiased gene profiling by microarray also confirmed expression of above genes in ExoPLAP- transcriptome. In addition, repeated measure ANOVA showed a significant change in the ExoPLAP transcriptome from T2-T4 (n=5/time point). Conclusion: ExoPLAP transcriptome changed with gestational age advancement in healthy women. The transcriptome expressed crucial placental genes involved in early embryonic development, such as actin cytoskeleton organization, appropriate cell positioning, DNA replication, and B-cell regulation for protecting mammalian fetuses from rejection. Thus ExoPLAP in maternal blood could be a promising source to study placental genes regulation for non-invasive monitoring of placental health.